2016
DOI: 10.1007/s10877-015-9822-4
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic method respiratory rate monitoring is useful in patients under intravenous anesthesia

Abstract: Respiratory depression can occur during intravenous general anesthesia without tracheal intubation. A new acoustic method for respiratory rate monitoring, RRa (Masimo Corp., Tokyo, Japan), has been reported to show good reliability in post-anesthesia care and emergency units. The purpose of this study was to investigate the reliability of the acoustic method for measurement of respiratory rate during intravenous general anesthesia, as compared with capnography. Patients with dental anxiety undergoing dental tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 18 publications
0
12
1
Order By: Relevance
“…Although studies document the reliability and validity of the devices, there is weak evidence that acoustic respiratory rate monitoring by itself reduces adverse events (Yang et al, 2017). There is evidence that in studies of postoperative respiratory depression, episodes of oxygen desaturation occurred that were not detected by changes in respiratory rate (Kawanishi, Inoue, & Kawaguchi, 2017;Ouchi, Fujiwara, & Sugiyama, 2017). Authors recommended pairing the acoustic respiratory rate monitor with pulse oximetry for more sensitive detection of OIRD (McGrath, Pyke, & Taenzer, 2017).…”
Section: Oxygen Saturationmentioning
confidence: 99%
“…Although studies document the reliability and validity of the devices, there is weak evidence that acoustic respiratory rate monitoring by itself reduces adverse events (Yang et al, 2017). There is evidence that in studies of postoperative respiratory depression, episodes of oxygen desaturation occurred that were not detected by changes in respiratory rate (Kawanishi, Inoue, & Kawaguchi, 2017;Ouchi, Fujiwara, & Sugiyama, 2017). Authors recommended pairing the acoustic respiratory rate monitor with pulse oximetry for more sensitive detection of OIRD (McGrath, Pyke, & Taenzer, 2017).…”
Section: Oxygen Saturationmentioning
confidence: 99%
“…We included a single study in the qualitative analysis but excluded it from the meta-analyses because the authors reported the data differently than in the other included studies. 22 Of the 8 excluded articles, 1 was excluded because it was available only in Spanish, 23 3 were excluded because the investigators compared capnography with a nonstandard comparison group, [24][25][26] 2 were excluded because they were not clinical studies, 27,28 and 2 were excluded because they enrolled pediatric patients. 29,30 The single study involving dental treatment 26 was among those we excluded because it had a nonstandard comparison group.…”
Section: Study Selectionmentioning
confidence: 99%
“…Previous study reported that adult patients with dental anxiety undergoing dental treatment under intravenous anesthesia without tracheal intubation were studied [1]. In this report, 11 patients with age of mean 38 years were enrolled.…”
Section: For Intravenous Anesthesia Without Tracheal Intubationmentioning
confidence: 99%
“…A new acoustic method for respiratory rate monitoring (RRa ® , Masimo Corp.) has shown good reliability when used in patients without tracheal intubation in dental operating room [1], postanesthesia care units [2,3], intensive care units [4], and emergency units [5]. Because there is no 'gold standard' for measurement of respiration rate, these reports were compared acoustic monitor with widely used methods (capnography or thoracic impedance pneumography).…”
Section: Introductionmentioning
confidence: 99%